IMPACT OF DIETARY REPLACEMENT OF INORGANIC ZINC WITH ORGANIC ZINC ON OVARIAN FOLLICULOGENESIS - NAGALAKSHMI, D; SADASIVA RAO, K; ARUNA KUMARI, G; SRIDHAR, K (The Indian Journal of Animal Reproduction, 2017)
Seventy-two weaned Sprague Dawley female rats (98.4±1.5 g) were randomly distributed to four dietary groups with six replicates in each and reared in polypropylene cages for 14 weeks. Dietary treatments were prepared by adding 12 ppm Zn to the basal diet (formulated with purified ingredients without Zn) from inorganic source (ZnCO3, control) and replacing inorganic Zn (Zni) at 0% (100i), 50% (50i:50o), 75% (25i:75o) and 100% (100o) with organic Zn (Zno, Zn methionine). All the rats were sacrificed at the end to collect the ovaries and the liver to study ovarian folliculogenesis and thiobarbituric acid reacting substances (TBARS), respectively. The dietary incorporation of Zno irrespective of level of replacement of Zni lowered (p
Keywords: Ovarian folliculogenesis; Rats; TBARS; Zinc methionine; ZnCO3